(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: This study examines the influence of organizational culture on implementation of strategic plans in the Insurance Industry in Kenya, with a keen focus on adhocracy culture, based on the Competing Values Framework (CVF). Adhocracy culture embodies innovation, adaptability, and flexibility; characteristics necessary for entities operating in highly dynamic environments. While much of the existing literature opines that organizational culture influences implementation of strategic plans, hardly any empirical study has tested this interrelation in an African setting, especially in a highly regulated and dynamic environment such as the Kenyan Insurance Industry. Applying cress-sectional survey data collected from 30 insurance companies and analyzed using regression methods, the output reveals that adhocracy culture is a statistically significant predictor of strategy execution (). On the contrary, market, clan, and hierarchy cultures, though popular in the industry, had no statistically significant influence on the success of strategy execution. These findings underscore the vitality of adaptive and innovation-driven organizational set ups in translating strategic plans into actionable results, particularly in highly dynamic and evolving markets where conventional and structured approaches are insufficient. The study advances the discourse in areas of organizational culture and corporate strategy by presenting empirical evidence from a dynamic and highly regulated industry in an underexplored developing economy. The study advances the logic that adaptive organizational cultures driven by innovation are necessary for effectual strategy execution. The study presents practical lessons for policymakers and leaders charged with execution of strategic plans. The study reckons that dynamic cultural attributes hugely enhance strategy implementation in highly dynamic business environments. It makes a recommendation that firms institutionalize innovation processes, set up flexible decision-making systems, and encourage cross-functional collaboration to enhance effective strategy execution.